Design of modified botulinum neurotoxin A1 variants with a shorter persistence of paralysis and duration of action. (1st December 2017) - Scheps, Daniel; López de la Paz, Manuela; Jurk, Marcel; Hofmann, Fred; Frevert, Jürgen
Abstract: Botulinum neurotoxins (BoNTs) are classified by their antigenic properties into seven serotypes (A-G) and in addition by their corresponding subtypes. They are further characterized by divergent onset and duration of effect. Injections of low doses of botulinum neurotoxins cause localized muscle paralysis that is beneficial for the treatment of several medical disorders and aesthetic indications. Optimizing the therapeutic properties could offer new treatment opportunities. This report describes a rational design approach to modify the pharmacological properties by mutations in the C-terminus of BoNT/A1 light chain (LC). Toxins with C-terminal modified LC's displayed an altered onset and duration of the paralytic effect in vivo . The level of effect was dependent on the kind of the mutation in the sequence of the C-terminus. A mutant with three mutations (T420E F423M Y426F) revealed a faster onset and a shorter duration than BoNT/A1 wild type (WT). It could be shown that the C-terminus of BoNT/A1-Lc controls both onset and duration of effect. Thus, it is possible to create a mutated BoNT/A1 with different pharmacological properties which might be useful in the therapy of new indications. This strategy opens the way to design BoNT variants with novel and useful properties. Highlights: 6 Mutants of Botulinum neurotoxin type A with mutation in the C-Terminus of the light chain were investigated. Two mutants with mutations in positions 420, 426 and 429 resulted in a faster onset and a shorter duration of effect. The potency of these two mutants in vivo was only slightly reduced in contrast to other mutants. The mutants are possible candidates for therapeutics for indications requiring only a short paralysis of injected muscleso.